Using Differentiated Instruction in Inclusive Schools: A Qualitative Analysis of Prospective Teachers’ Self-Efficacy - Tayiba Iqbal, Yaar Muhammad (JIE, 2020)
This qualitative study explored prospective teachers’ self-efficacy beliefs regarding using differentiated instruction in inclusive schools. The sample of the study was 16 prospective teachers attending a prestigious private university in Lahore and learning how to teach students with diverse needs in inclusive schools. The prospective teachers voluntarily agreed to participate. With the help of a theoretical framework on differentiated instruction, an interview guide was designed, and a semi-structured interview was conducted with each participant individually for an in-depth exploration of teacher’s self-efficacy beliefs regarding different themes of instruction differentiation. All interviews were audio recorded and later transcribed. Data were analyzed using the template analysis method. Findings revealed that most of the prospective teachers were confident in differentiating instruction for diversity.